A urinary metabolite constellation to detect acute rejection in kidney allografts - Banas, Miriam C.; Neumann, Sindy; Pagel, Philipp; Putz, Franz Josef; Krämer, Bernhard K.; Böhmig, Georg A.; Eiglsperger, Johannes; Schiffer, Eric; Ruemmele, Petra; Banas, Bernhard (EBioMedicine, 2019)
Background: To validate a novel method for post-transplant surveillance to detect kidney allograft rejection via a characteristic constellation of the urine metabolites alanine, citrate, lactate, and urea investigated by nuclear magnetic resonance (NMR) spectroscopy a first prospective, observational study was performed. Methods: Within the UMBRELLA study 986 urine specimens were collected from 109 consecutively enrolled renal transplant recipients, and metabolite constellations were analyzed. A metabolite rejection score was calculated and compared to histopathological results of corresponding indication and protocol allograft biopsies (n = 206). Findings: The metabolite constellation was found to be a useful biomarker to non-invasively detect acute allograft rejection (AUC = 0.75; 95% confidence interval (CI) 0.68–0.83; based on 46 cases and 520 control samples). Combined analysis of the metabolite rejection score and the estimated glomerular filtration rate (eGFR) at the time of urine sampling further improved the overall test performance significantly (AUC = 0.84; 95% CI 0.76–0.91; based on 42 cases and 468 controls). Regarding the time course analysis in patients without rejection episodes the test results remained well below a diagnostic threshold associated with high risk of acute rejection. In other cases, a marked increase above this threshold indicated acute allograft rejection already six to ten days before diagnostic renal biopsies were performed. Interpretation: A combination of an NMR-based urine metabolite analysis and eGFR is promising as a non-invasive test for post-transplant surveillance and to support decision making whether renal allografts need histopathological evaluation.
CRIS-Team Scopus Importer:2019-10-29
Keywords: Biomarker; Kidney transplant rejection; NMR-spectroscopy; Non-invasive test; Urinary metabolites